Serving America's veterans : a reference handbook - Korb, Lawrence J., 1939- (Santa Barbara, Calif. : Praeger Security International, 2009)
"In this handbook, Korb and his team of experts survey, analyze, and evaluate the infrastructural conditions, administrative and health care service challenges, policies, and politics affecting veterans affairs in the United States."-inside jacket.
Introduction / Lawrence J. Korb -- The history of Veterans Affairs / Peter M. Juul -- The impact of veterans on the American political system / Max A. Bergmann -- Veteran demographics: today's population, tomorrow's projections / Sean E. Duggan -- Administrative barriers to accessing VA health care and benefits / Sean E. Duggan -- Multiple epidemics in veterans' mental health / Sean E. Duggan -- Conclusion / Lawrence J. Korb.
Includes bibliographical references and index.
Keywords: Veterans -- Services for -- United States -- Handbooks, manuals, etc; Veterans -- Medical care -- United States -- Handbooks, manuals, etc; Veterans -- Mental health services -- United States -- Handbooks, manuals, etc; United States. -- Department of Veterans Affairs -- Handbooks, manuals, etc; Demography -- United States; Mental health services -- United States; Veterans Health -- United States